Cytotoxic study of Knema laurina and Antidesma orthogyne extracts on human breast cancer cell line MCF-7 - Sama, Shaban; Bakhtiar, M. Taher; Ichwan, Solachuddin J. A. (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2016)
Cancer is a disease that is characterized by the abnormal cell differentiation and maturation as well as uncontrolled cell growth. For several decades’ various types of different human cancer cell lines have been extensively used as an in vitro model to understand the mechanisms of carcinogenesis and to discover new treatment modalities, including the usage of natural compounds those are believed to have anticancer activity. The MCF-7 human breast cancer cell line is one of the cell lines that has been widely utilized for anti-cancer drug development. In this study, MCF-7 will be used to investigate bioactive potential(s) of two natural extracts Knema laurina and Antidesma orthogyne extracts to suppress MCF-7 cell growth by using MTT assay.